1990
DOI: 10.1113/jphysiol.1990.sp017934
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal activity related to head and eye movements in cat superior colliculus.

Abstract: SUMMARY1. Movement-related discharges were recorded from single cells in the superior colliculus of alert cats while they made eye saccades (with head fixed) or gaze saccades (with head free).2. Visual and auditory stimuli were used as saccade targets. In addition, saccades were made to the remembered location of targets and spontaneously, in the absence of targets, during intertrial intervals.3. When the head was still and the cat performed either spontaneous saccades or saccades to remembered targets, only o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

1993
1993
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(22 citation statements)
references
References 45 publications
1
21
0
Order By: Relevance
“…B Dierence between the pre-and postlesional size of saccades as a function of the distance between the activated Qv and the lesioned TLLB unit. Negative size indicates hypometric postlesional saccades, while negative distance indicates that the Qv unit is rostral to (has a smaller index number than) the TLLB unit account for the fact that tectal presaccadic cells which burst before saccades in one direction are inhibited during saccades in the opposite direction (Infante and Leiva 1986;Peck 1990). Similarly, the herein proposed model does not employ a well-known projection to the SC that originates in the zona incerta.…”
Section: Anatomy and Neurophysiologymentioning
confidence: 81%
“…B Dierence between the pre-and postlesional size of saccades as a function of the distance between the activated Qv and the lesioned TLLB unit. Negative size indicates hypometric postlesional saccades, while negative distance indicates that the Qv unit is rostral to (has a smaller index number than) the TLLB unit account for the fact that tectal presaccadic cells which burst before saccades in one direction are inhibited during saccades in the opposite direction (Infante and Leiva 1986;Peck 1990). Similarly, the herein proposed model does not employ a well-known projection to the SC that originates in the zona incerta.…”
Section: Anatomy and Neurophysiologymentioning
confidence: 81%
“…Extracellular recording of local field potentials or single-cell activity showed that visual responses in the superficial layers of the SC are inhibited by stimulation of the contralateral SC (Goodale 1973;Hoffmann and Straschill 1971;Mascetti and Arriagada 1981;Robert and Cuénod 1969). Similarly, tectal output neurons related to saccadic eye movements were found to be inhibited during ipsiversive orienting movements (Infante and Leiva 1986;Peck 1990) or by electrical stimulation of the contralateral SC (Munoz and Istvan 1998). With regard to these physiological studies, the anatomical features of commissural connections between the two SCs have been examined extensively (Behan and Kime 1996a;Edwards 1977;Fish et al 1982;Grantyn and Grantyn 1982;Magalhães-Castro et al 1978;Moschovakis and Karabelas 1985;Olivier et al 1998;Rhoades et al 1986;Yamasaki et al 1984).…”
Section: Introductionmentioning
confidence: 95%
“…Likewise in the monkey, phasic responses in midbrain DA neurons have been described to auditory and simple visual stimuli which signal trial onset (Bayer and Glimcher, 2005;, and to the opening of a food box following training with food (Romo and Schultz, 1989;1990). They are also activated by simple visual stimuli (Schultz et al, 1993) and simple visual stimuli combined with auditory stimuli (Bayer and Glimcher, 2005) when associated with reward within a task.…”
Section: Stimulimentioning
confidence: 99%
“…In the case of vision, the short latency of the phasic DA responses led us to investigate the possibility that a subcortical visual structure, the superior colliculus (SC), rather than a cortical relay, might be the critical source of afferent visual input (Comoli et al, 2003, Dommett et al, 2005. Visual response latencies of SC neurons (40-60 ms - Wurtz and Albano, 1980, Munoz and Guitton, 1986, Jay and Sparks, 1987, Peck, 1990, Stein and Meredith, 1993, are consistently shorter than those of DA neurons (70-100 ms - Schultz, 1998, Morris et al, 2004, Takikawa et al, 2004, whilst responses in cortical regions responsible for feature detection and object recognition are approximately the same or longer (80-130 ms; Fabre-Thorpe, 2001, Rousselet et al, 2004).…”
Section: Elucidating the Circuitrymentioning
confidence: 99%
See 1 more Smart Citation